(1/2-1/3)^3: (1/3-1/4)^2•(3/2)^2 ответ по действиям

Охико14 Охико14    2   07.06.2019 14:00    1

Ответы
artemix01 artemix01  01.10.2020 21:28
(1/2-1/3)^3:(1/3-1/4)^2•(3/2)^2=3/2
1/2-1/3=(3-2)/6=1/6
1/3-1/4=(4-3)/12=1/12
(1/6)^3=1/6^3
(1/12)^2=1/(2*6)^2
1/6^3 : 1/(2*6^2)=1/6^3*(2*6)^2=4/6=2/3
2/3*(3/2)^2=3/2=1 1/2 =1.5
(1/2-1/3)^3: (1/3-1/4)^2•(3/2)^2 ответ по действиям
ПОКАЗАТЬ ОТВЕТЫ
egorkovalev000007 egorkovalev000007  01.10.2020 21:28
. . . . . . . . . . . . . . и . .
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика